MANFAAT INTERNET BAGI AUDITOR - ., Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2006)
Abstract Revolution information technology that happened in this time push company to exploit computer technology to execute various activity of operational activity and managerial. Technological of exploited computer alter accountancy data process method, from manual process method become process method base on computer technology. Auditor, as one of the parties related to entrepreneur circle, have to continue to perceive every growth that happened in business world, including various hardware and used software to support company performance in improving business activity effectiveness and efficiency. This change 'forcing' auditor have to can adapt by various existing growth and change, including accountancy practice growth which medium happened and which possible earn happened. Keywords : Internet, Auditor, Technological computer